Synthesis of unsaturated diesters of primary, secondary and tertiary diols derived from dimethyl (+)-tartrate and galactaric acid - Scoccia, Jimena (2013)
The preparation of symmetrical unsaturated diesters of dioe first was the reaction of mixed anhydrides, obtained from α,β-unsaturated acids and benzoyl chloride, with diols 3 (primary), 5 (secondary), and 7 (primary), i.e., Yamaguchi-SantaLucía's method, however only the symmetrical diacrylates of diols 5 and 7 were obtained quantitatively. In the other ten cases studied the reactions led to mixtures of symmetrical and unsymmetrical diesters that were difficult to separate. The mixed anhydrides did not react with the tertiary diols 4 (TADDOL) and 8. The average yield obtained in desired symmetrical diesters in the 12 cases studied was 54 %. The acylation of the diols with the anhydrides of the unsaturated acids, was found to be an excellent method, leading to the symmetrical unsaturated diesters of diols 3, 5, 7 as the only products of reaction, in an average yield of 83 %. Unfortunately, the method could not be applied to diesters derived from the tertiary diols 4 (TADDOL) and 8. The third method studied was the reaction between the alkoxides prepared with solutions of nBuLi in ether with the unsaturated acid chlorides at-50 °C, i.e., the Kaiser-Woodruff protocol. This was found to be the best of the three methods tested. The method was applied with success to the synthesis of the desired unsaturated diesters derived from diols 3-5, 7, and 8. The average yield of the 19 cases studied was 78 %.